Contemporary British autoethnography - Turner, Lydia; Grant, Alec; Short, Nigel P. (Studies in Professional Life and Work, 2013)
This engaging, informative book makes an exciting contribution to current discussions about the challenges and uses of contemporary autoethnography. Authors from a range of disciplines 'show and tell' us how they have created autoethnographies, demonstrating a rich blend of theories, ethical research practices, and performances of identities and voice, linking all of those with the socio-cultural forces that impact and shape the person. The book will be a useful resource for new and experienced researchers; academics who teach and supervise post-graduate students; and practitioners in social science who are seeking meaningful ways to conduct research. This should be required reading for all qualitative research training.